Harnessing Neutrophil Survival Mechanisms during Chronic Infection by Pseudomonas aeruginosa: Novel Therapeutic Targets to Dampen Inflammation in Cystic Fibrosis - Marteyn, Benoît S.; Burgel, Pierre-Régis; Meijer, Laurent; Witko-Sarsat, Véronique (Frontiers in Cellular and Infection Microbiology, 2017)
More than two decades after cloning the cystic fibrosis transmembrane regulator (CFTR) gene, the defective gene in cystic fibrosis (CF), we still do not understand how dysfunction of this ion channel causes lung disease and the tremendous neutrophil burden which persists within the airways; nor why chronic colonization by Pseudomonas aeruginosa develops in CF patients who are thought to be immunocompetent. It appears that the microenvironment within the lung of CF patients provides favorable conditions for both Pseudomonas aeruginosa colonization and neutrophil survival. In this context, the ability of bacteria to induce hypoxia, which in turn affects neutrophil survival is an additional level of complexity that needs accounted for when controlling neutrophil fate in CF. Recent studies have underscored the importance of neutrophils in innate immunity and their functions appear to extend far beyond their well-described role in antibacterial defense. Perhaps a disturbance in neutrophil reprogramming during the course of an infection severely modulates the inflammatory response in CF. Furthermore there is an emerging concept that the CFTR itself may be an immune modulator and stimulating CFTR function in CF patients could promote neutrophil and macrophages antimicrobial function. Fostering the resolution of inflammation by favoring neutrophil apoptosis could preserve their microbicidal activities but decrease their proinflammatory potential. In this context, triggering neutrophil apoptosis with roscovitine may be a potential therapeutic option and this is currently being evaluated in CF patients. In the present review we discuss how neutrophils functions are disturbed in CF and how this may relate to the chronic infection with P. aeuginosa and propose novel research directions aimed at modulating neutrophil survival, dampening lung inflammation and ultimately leading to an amelioration of the lung disease.